2014
DOI: 10.1037/h0100575
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of multiple exemplar instruction to teach perspective-taking skills to adolescents with Asperger Syndrome.

Abstract: The goal of this study was to investigate the effects of multiple exemplar instruction for teaching perspective-taking skills Ruth Anne Rehfeldt to young adults with autism. Using a multiple probe design, participants were trained and tested using protocols evaluating the deictic frames of I-You, Here-There, and Now-Then. Generalization of perspective-taking skills was evaluated using two standardized assessments designed to evaluate theory of mind, which were administered at pre and posttest. Generalization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 14 publications
3
25
0
4
Order By: Relevance
“…One limitation in this growing area of research is that participants who demonstrated a transfer of function were either typically developing (Rehfeldt et al, 2007;Weil et al, 2011) or had mild forms of autism (Lovett & Rehfeldt, 2014); demonstration of such transfers in children with more…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation in this growing area of research is that participants who demonstrated a transfer of function were either typically developing (Rehfeldt et al, 2007;Weil et al, 2011) or had mild forms of autism (Lovett & Rehfeldt, 2014); demonstration of such transfers in children with more…”
mentioning
confidence: 99%
“…Three studies have since evaluated the use of deictic relational training in application with individuals with autism (Gilroy, Lorah, Dodge, & Fiorello, 2015;Jackson, Mendoza, & Adams, 2014;Lovett & Rehfeldt, 2014). One limitation in this growing area of research is that participants who demonstrated a transfer of function were either typically developing (Rehfeldt et al, 2007;Weil et al, 2011) or had mild forms of autism (Lovett & Rehfeldt, 2014); demonstration of such transfers in children with more severe forms of autism would suggest that deictic relating as a generalized operant (see Hayes et al, 2001) had occurred. Therefore, the purpose of the study was to evaluate the efficacy of a relational training procedure in teaching singlereversal deictic relational responding to individuals with autism.…”
mentioning
confidence: 99%
“…Due to its importance, the topic of perspective-taking has amassed a large body of research that spans several decades and theoretical approaches (e.g., Baron-Cohen, 2001;Brüne, 2005;Dennett, 1987;Dvash & Shamay-Tsoory, 2014;Smith, 2006;Wellman, Cross, & Watson, 2001). Although much of this research has been conducted by developmental and cognitive psychologists through the lens of predictive science, a growing body of functional contextual research based in Relational Frame Theory (RFT; Hayes et al, 2001) is aimed at understanding how environmental variables can be manipulated to achieve influence over derived perspective-taking behavior (e.g., Belisle, Dixon, Stanley, Munoz, & Daar, 2016;Gilroy, Lorah, Dodge, & Fiorello, 2015;Heagle & Rehfeldt, 2006;Jackson, Mendoza, & Adams, 2014;Lovett & Rehfeldt, 2014;Rehfeldt, Dillen, Ziomek, & Kowalchuk, 2007;Rendón, Soler, & Cortés, 2012;Weil, Hayes, & Capurro, 2011). Before elaborating on how RFT has guided my approach to influencing derived perspective-taking in the present investigation, it will be useful to first provide some context with respect to how perspective-taking is approached in the cognitive and developmental literature, and then review RFT's more general characterization of cognition.…”
mentioning
confidence: 99%
“…Podobnie jak wyniki testów teorii umysłu, badacze w nurcie RFT sugerują rozwojowy trend w zakresie zdolności przyjmowania perspektywy (Barnes-Holmes i in., 2004). Umiejętności tych można skutecznie uczyć zarówno dzieci typowo rozwijające się (Heagle, Rehfeldt, 2006;Weil i in., 2011), jak i te o zaburzonym rozwoju (Rehfeldt i in., 2007;Lovett, Rehfeldt, 2014). I badacze, i praktycy pracujący w nurcie RFT sugerują, że nabywanie umiejętności wywodzenia relacji deiktycznych rozwija się w miarę doskonalenia wcześniejszych (mniej abstrakcyjnych) zdolności reagowania relacyjnego, takich jak koordynacja czy porównanie (McHugh i in., 2009;Barnes-Holemes, Kavanagh, Murphy, 2016).…”
Section: Relacje Deiktyczne a Przyjmowanie Perspktywyunclassified